Lactate Thresholds and the Simulation of Human Energy Metabolism: Contributions by the Cologne Sports Medicine Group in the 1970s and 1980s - Wackerhage, Henning; Gehlert, Sebastian; Schulz, Henry; Weber, Sebastian; Ring-Dimitriou, Susanne; Heine, Oliver (Frontiers in Physiology, 2022)
Today, researchers, practitioners, and physicians measure the concentration of lactate during a graded exercise test to determine thresholds related to the maximal lactate steady state (maxLass) as a sensitive measure of endurance capacity. In the 1970s and 1980s, a group of Cologne-based researchers around Wildor Hollmann, Alois Mader, and Hermann Heck developed the methodology for systematic lactate testing and introduced a 4 mmol.L−1 lactate threshold. Later, they also developed the concept of the maxLass, and Mader designed a sophisticated mathematical model of human energy metabolism during exercise. Mader`s model simulates metabolic responses to exercise based on individual variables such as maximum oxygen uptake (V˙O2max) and the maximal rate of lactate formation (νLa.max). Mader’s model predicts that the νLa.max reduces the power at the anaerobic threshold and endurance performance but that a high νLa.max is required for events with high power outputs in elite athletes. Mader’s model also assumed before the millennium that the rate of fat oxidation is explained by the difference between glycolytic pyruvate synthesis and the actual rate of pyruvate oxidation which is consistent with current opinion. Mader’s model also simulated the V˙O2max slow component in the mid-1980s. Unfortunately, several landmark studies by the Cologne group were only published in German, and as a result, contributions by the Cologne group are under-appreciated in the English-speaking world. This narrative review aims to introduce key contributions of the Cologne group to human metabolism research especially for readers who do not speak German.